2012 12th International Conference on Quality Software 2012
DOI: 10.1109/qsic.2012.41
|View full text |Cite
|
Sign up to set email alerts
|

Redefinition of Fault Classes in Logic Expressions

Abstract: Fault-based testing selects test cases to detect hypothesized faults. In logic expression testing, many fault classes have been defined by researchers based on the syntax of the expressions. Due to the syntactic nature of the logic expressions, some fault classes may exist in one form (say, disjunctive normal form -DNF) of the logic expressions but not in other forms (say, general form). As a result, different faultbased testing techniques have been developed for different types of logic expressions and these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Common faults that might occur during the programming process have been carefully investigated and summarized [31,32]. The described typical programming errors involve missing or extra literals/variables, and the use of incorrect operators and operands.…”
Section: Experimental Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Common faults that might occur during the programming process have been carefully investigated and summarized [31,32]. The described typical programming errors involve missing or extra literals/variables, and the use of incorrect operators and operands.…”
Section: Experimental Settingsmentioning
confidence: 99%
“…For instance, VNF (Variable Negation Fault) is quite misleading: It is unsure whether it refers to the negation of all occurrences of a variable or one occurrence of a variable. A very precise definition of every fault type is provided in [32]. In this study, we used ten types of faults for general Boolean expressions in our previous work [7].…”
Section: Experimental Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fault‐based Boolean expression testing, researchers have classified faults into a number of fault classes 4,7‐9 . Researchers have also identified that literal insertion faults (LIFs) are very hard to detect as compared to other fault classes 7,8,10 .…”
Section: Introductionmentioning
confidence: 99%
“…In[52], 15 fault classes were defined. Since IDNF expressions do not have parenthesis, we do not generate POF and PSF faulty expressions.…”
mentioning
confidence: 99%